CORRIGENDUM / ERRATUM / RETRACTION - Yulianto Ade Prasetya (Al-Kauniyah: Jurnal Biologi, 2018)
RETRACTION TO: Prasetya, Y., A. (2018). Deteksi Gen SHV pada Isolat Klinik Esherichia coli Penghasil Extended Spectrum Beta−Lactamases (ESBLs) dengan Metode Polymerase Chain Reaction (PCR) dari Urin Pasien di RSUD Dr. Soetomo Surabaya. AL-KAUNIYAH: Jurnal Biologi, 11(2), 2018, 91-98. doi:10.15408/kauniyah.v11i2.5779.This article has been retracted by Publisher based on the following reason: The Editor of AL-KAUNIYAH Journal found the double publications in the article publishing due to article's content similarity published in Bioeksperimen: Jurnal Penelitian Biologi Vol 4, No. 2 (2018) URL: http://journals.ums.ac.id/index.php/bioeksperimen/article/view/6884. Titled “Deteksi Gen SHV pada Isolat Klinik Eschericia coli Penghasil Extended Spectrum Beta-Lactamases (ESBLs) dari Urin Pasien di RSUD Dr. Soetomo Surabaya” with the same author who is Yulianto Ade Prasetya. Based on clarification, Author of the article have admitted that he has published the same article published in Bioeksperimen: Jurnal Penelitian Biologi Vol 4, No. 2 (2018).One of the conditions of submission of paper for publication in this journal is that authors declare explicitly that their work is original and has not appeared in a publication elsewhere. Re-use of any data should be appropriately cited. As such this article represents a severe abuse of the scientific publishing system. The scientific community takes a very strong view on this matter and apologies are offered to readers of the journal that this was not detected during the submission process.